THE PEMBERIAN CORE EXERCISE MENINGKATKAN JANGKAUAN THROW-IN PADA SISWA SEKOLAH SEPAK BOLA BALI SOCCER BALL USIA 11-13 TAHUN - Choirul Anwar; Ni Wayan Tianing; Made Niko Winaya (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2015)
Throw-in is one of the basic techniques in football which aims to start thegame again after the ball out of left field through the side lines. To generate a throw-in that muchneeded donations abdominal and back muscle strength followed by hand muscles strength. Methods:This study uses a true experiment, the design of two group pre-test and post-test design. Samples are32 people were divided into two groups consisting of Group 1 get treatment core exercise and group 2without treatment. Results: Paired Sample T test in Group 1 showed P = 0.000 difference in the meanincrease of 2,79 meters and the percentage is 21,24%, while Group 2 showed P=0,000 difference inmean improvement of 0,70 meters and the percentage is 5,34%. On different with IndependentSample T test, showing the result P=0,000, because of p value <0,05, it means there is a significantdifference between the core exercise’s group (first group) and second group. In increasing the rangeof throw-in. Conclusion: The aplication of core core exercise can give a significant difference forimproving the value range of throw-in rather than without getting a treatment.